The Role of Speculative Factor in the Indonesian Stock Price Determination - Soemarso Slamet Rahardjo (Economics and Finance in Indonesia, 2015)
This study observes the speculative element in the price determination and its mean reverting pattern. The existence of speculative element in the Indonesian stock market price determination was proven. Exponential Generalized Auto Regressive Conditional Heteroscedasticity (EGARCH) method indicates the non-stationary process of the residuals. There are systematic as well as unsystematic component embedded in the speculative behavior. Vector Error Correction Model (VECM) concludes that prices contain volatilities in the short run, but, it will revert to the mean in the long run. Investors’ behavior are neutral toward expected gain vis a vis losses in a stock trading.